2019
DOI: 10.1155/2019/5904801
|View full text |Cite
|
Sign up to set email alerts
|

Research on Grid Scroll Chaotic Extended Sequence Algorithm and Its Circuit Implementation for F‐OFDM System

Abstract: High peak-to-average power ratio (PAPR), a main problem of 5G Filtered-Orthogonal Frequency Division Multiplexing (F-OFDM) system, seriously affects the system’s transmission efficiency. Aiming at the shortcomings of the traditional selective mapping (SLM) algorithm, the grid scroll chaotic extended sequence (GSCES) algorithm is proposed to solve the high PAPR problem. The proposed grid multiscroll chaotic maps are used as random phase sequence vectors instead of the traditional pseudo random sequence, which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Investigations have shown that a variety of ecological systems display chaotic behaviours [8,9]. In recent years, chaotic systems that display multiscroll [10][11][12] and multiwing [13] chaotic attractors were considered in the literature. Zhang et al studied the dynamics of a New 5D Hyperchaotic system of Lorenz type and obtained the global exponential attractive set and the ultimate bound set for this system of Lorenz Type [14].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have shown that a variety of ecological systems display chaotic behaviours [8,9]. In recent years, chaotic systems that display multiscroll [10][11][12] and multiwing [13] chaotic attractors were considered in the literature. Zhang et al studied the dynamics of a New 5D Hyperchaotic system of Lorenz type and obtained the global exponential attractive set and the ultimate bound set for this system of Lorenz Type [14].…”
Section: Introductionmentioning
confidence: 99%